2022
DOI: 10.1093/mnras/stac945
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental differences in the properties of red and blue quasars: measuring the reddening and accretion properties with X-shooter

Abstract: We have recently found fundamental differences in the radio properties of red quasars when compared to typical blue quasars. In this paper we use data from the X-shooter spectrograph on the Very Large Telescope, providing spectral coverage from ∼3000–25000 Å, of a sample of 40 red and blue luminous quasars at 1.45 < z < 1.65 to explore the connections between the radio, emission-line, and accretion-disc properties. We fit various dust-extinction curves to the data and find that dust reddening can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 103 publications
1
8
0
Order By: Relevance
“…To provide a glimpse of the overall spectral diversity of targets in the QSO survey, in Figure 13 we plot the DESI spectra for individual QSOs, selected to cover a broad range in spectral diversity. 55 Each composite spectrum is constructed following the approach outlined in Fawcett et al (2022). Briefly, the ends of each contributing spectrum are trimmed to remove noisy data and then corrected for Galactic extinction and shifted to rest-frame wavelengths using the VI redshift.…”
Section: A Glimpse Of the Spectral Diversity In The Qso Surveymentioning
confidence: 99%
“…To provide a glimpse of the overall spectral diversity of targets in the QSO survey, in Figure 13 we plot the DESI spectra for individual QSOs, selected to cover a broad range in spectral diversity. 55 Each composite spectrum is constructed following the approach outlined in Fawcett et al (2022). Briefly, the ends of each contributing spectrum are trimmed to remove noisy data and then corrected for Galactic extinction and shifted to rest-frame wavelengths using the VI redshift.…”
Section: A Glimpse Of the Spectral Diversity In The Qso Surveymentioning
confidence: 99%
“…Indeed, the strong UV/X-ray radiation of WLQs and super-Eddington NLS1s can trigger a powerful disk wind, which may have a clumpy nature and cover a wide viewing angle (e.g., Ohsuga & Mineshige 2011;Takeuchi et al 2014;Hagino et al 2016). This clumpy wind offers a natural explanation for the drastic X-ray variability observed in both WLQs and WLQ-like Seyferts (Miniutti et al 2012;Reeves et al 2020;Jin et al 2022b) and the statistical transition of red quasars evolving into blue quasars (Temple et al 2019;Fawcett et al 2022), as well as the transformation of broad absorption lines observed recently in some WLQs (Yi et al 2019(Yi et al , 2022. Then, the observations of the two WLQ-like Seyferts with totally different reddening values support the idea that a similar disk wind scenario is applicable for both WLQs and WLQ-like Seyferts (Jin et al 2022a), although their black hole masses differ by more than one order of magnitude.…”
Section: Emission Line Spectrummentioning
confidence: 99%
“…12. 8 8 Each composite spectrum is constructed following the approach outlined in Fawcett et al (2022). Briefly, the ends of each contributing spectrum are trimmed to remove noisy data and then corrected for Galactic extinction and shifted to rest-frame wavelengths using the VI redshift.…”
Section: Investigating the Differences Between The Redrock Quasars An...mentioning
confidence: 99%